Covariance mapping of two-photon double core hole states in C2H2 and C2H6 produced by an x-ray free electron laser. (2nd July 2015) - Mucke, M; Zhaunerchyk, V; Frasinski, L J; Squibb, R J; Siano, M; Eland, J H D; Linusson, P; Salén, P; Meulen, P v d; Thomas, R D; Larsson, M; Foucar, L; et al.
Abstract: Few-photon ionization and relaxation processes in acetylene (C2 H2 ) and ethane (C2 H6 ) were investigated at the linac coherent light source x-ray free electron laser (FEL) at SLAC, Stanford using a highly efficient multi-particle correlation spectroscopy technique based on a magnetic bottle. The analysis method of covariance mapping has been applied and enhanced, allowing us to identify electron pairs associated with double core hole (DCH) production and competing multiple ionization processes including Auger decay sequences. The experimental technique and the analysis procedure are discussed in the light of earlier investigations of DCH studies carried out at the same FEL and at third generation synchrotron radiation sources. In particular, we demonstrate the capability of the covariance mapping technique to disentangle the formation of molecular DCH states which is barely feasible with conventional electron spectroscopy methods.